MORPHOMETRIC SIPUT SEDOT (Cerithidea cingulata) AND SIPUT PINANG (Littoraria melanostoma) IN MANGROVE ECOSYSTEM AT INDUSTRIAL AND NON INDUSTRIES AREAS OF SUNGAI SEMBILAN DISTRICT DUMAI CITY, RIAU PROVINCE - Nur Arfah; Sofyan H. Siregar; Bintal Amin (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
AbtrakThis research was conducted in May 2018 in the Mangrove Ecosystems at industrial and non-industrial areas of Sungai Sembilan District, Dumai City, which aimed to determine the morphometrics  and the lenght-weight relationship of C. cingulata and L. Melanostoma.Survey method was appled by using line transect at 2 stations, namely in the industrial area (PT. Ivo mas, PT. Sinar Mas, PT. Energi Sejahtera Mas) and non industrial area (Sungai Teras). The results showed that the morphometrics of C.cingulata and L. melanostoma at each station had different sizes. In industrial area,C. cingulatahas larger and wider than larger of size non industrial zone. On the other hand in the non industrial area,L. melanostomahas larger and wider than larger  of size industrial zone. The relationship between length and weight of C.cingulata infor industri at area is negative allometric, but  it was positive allometric for non industrial zone. Meanwhile the length and weight of L.melanostoma in both areas are negative allometric and they have strong correlation values (r= 0,99 dan 1). Keywords: Morphometrics, Cerithidea cingulata, Littoraria melanostoma, Dumai